Utility of CT Scan in Assessment of Paranasal Sinus Pathology - Praveen Kumar Monagari (Asian Journal of Medical Research, 2019)
Background: Paranasal sinuses are a group of four paired air-filled spaces that surround the nasal cavity. The present study was conducted to assess utility of CT scan in assessment of paranasal sinus pathologies. Subjects and Methods: The present study was conducted on 96 patients with pathologies of PNS of both genders. All patients were subjected to CT scan using Planmica machine. Results: Age group 20-30 years had 32 patients, 30-40 years had 38 patients and 40-50 years had 14 patients and > 50 years had 12 patients. The difference was significant (P< 0.05). Common pathologies were inflammatory seen in 40 patients, sinusitis in 32, neoplastic in 8, polyposis in 6, sinus hypoplasia in 5 and others in 4 patients. The difference was significant (P< 0.05). CT findings were sclerosis seen in 2 benign and 1 malignant lesions, erosions 1 each in benign and malignant, thinning 1 each in benign and malignant and increase sinus size 1 in malignant lesions. Conclusion: Authors found that CT scan is useful in assessment of lesions of paranansal sinus. Common pathologies were inflammatory, sinusitis, neoplastic, polyposis and sinus hypoplasia.